Assessing the OECD Countries’ Industry 4.0 Maturity from Sustainable Development Goals’ Perspective: An Integrated PCA and DEA Approach - Egilmez, Gokhan; Tutore, Ilaria (Journal of Knowledge Management Practice, 2025)
Industry 4.0 (I4.0) technologies and relevant research initiatives have been at the focal point of sustainable industrial development initiatives. Adoption of these technologies require a maturity level to create sustainable economic, social, and environmental benefits to society. In this study, we investigated the I4.0 maturity in OECD countries. A two-phase methodology is proposed: principal component analysis (PCA) and data envelopment analysis (DEA). The main contribution of the study to the state-of-art is a statistically reliable analytical framework which yields I4.0 maturity score from relevant United Nations Sustainable Development Goals’ perspectives. Results indicate that the proposed two-phase method significantly reduces the potential multi-collinearity impacts on I4.0 maturity performance. Moreover, USA, Sweden, Finland, and Switzerland were found to the on the efficiency frontier in terms of I4.0 maturity whereas Turkey, Chile, Latvia, and Mexico were found to be in the lowest ranks which need substantial policy implementation to increase their digitalization efforts.